Enzymatic hydrolysates of grain and products of its processing. A review of the subject field - I. S. Vitol; E. P. Meleshkina (Пищевые системы)
The paper presents a review of scientific publications devoted to investigation of an action of enzyme preparations and their compositions on various grain substrates, production of enzymatic hydrolysates and structurally modified secondary products of grain processing. Depending on the set goals, the main of which is the industrial use of products of enzymatic modification, a method is proposed for separation of hydrolysates into two groups: (1) with isolation and purification of protein from ballast compounds with the following hydrolysis and (2) without preliminary isolation of protein. The present review is based on the results of studies by national and foreign scientists with the use of search systems and databases: eLibrary, CyberLeninka, Google Scholar, ScienceDirect, Springer open, PubMed. Analysis of the subject field shows a very wide range of publications related to characteristics of enzymatic hydrolysates produced using biopolimers of animal and plant raw materials as a substrate. Over the last ten years, the number of studies on enzymatic modification of various types of grain and leguminous crops, and composite grain mixtures has increased significantly; the possibilities of their use as enriching, functional-technological and functional components of feedstuff and food products have been studied. The revival of the microbiological branch, including production of domestic enzyme preparations, is based on experimental studies on the search for new producer strains and improvement of methods for isolation, purification and stabilization of enzymes. All studies by national and foreign authors support the topicality and good prospects of increasing a range of the use of enzymatic hydrolysates obtained from the grain raw material and secondary products of its processing in various areas of the feedstuff production, food industry and pharmacology.